Olena Tkachuk. Humanistic plane of british imperialism in Goseph Conrad’s artistic world. - Olena Tkachuk (Philological Treatises, 2020)
The article is devoted to the problem of imperial discourse in the works by Joseph Conrad. Despite the monolithic system of coordinates and the principled position of Edward Said concerning the imperial intervention, researchers offer alternative models of imperial engagement. Most often, researchers consider a large number of imperial texts to be a single concept. Sara Mills, Peter Hulme, Mary Louise Pratt, Anne McClintock, Peter Cane, Antony Hopkins believe the factors affecting the specificity of imperialism must be taken into account primarily in the context of history, politics and economics. Scientists are convinced that colonialism is not only a destructive and exploitative system. Very often, the representatives of English nation mastered new territories peacefully, through trade, bribery, gifts and, often, marriages with local women. Similar intercultural connections are represented in such works of Joseph Conrad as "Almayer’s Folly," "An Outcast of the Islands," "The Rescue: A Romance of the Shallows." Adapted to English culture and acclimatized in English society, organically perceived the British imperial appeal, the writer remained at the positions of humanism in the conquest of territories. The peculiarities of the imperial and anti-imperial aspects of Conrad’s world were studied by Georges Jean-Aubry, Cedric Watts, Lynn Sutherland, Anthony Fothergill, Henryk Zins, Benita Parry, Jacques Darras, but the researchers have not paid their attention yet to the various forms of cooperation of the local population with representatives of "civilized" peoples.